Character Education Based on Local Wisdom in Learning Science: A Systematic Literature - Novitasari, Naintyn; Walid, Ahmad (PPSDP International Journal of Education, 2024)
Character education based on local wisdom is an effort to prevent the decline of ethical and moral values among the younger generation in the educational process. This literature review aims to discuss the cultivation of local wisdom-based character education for students within science learning. The method used in this study is a Narrative Literature Review (NLR). Data collection was conducted through the Science Direct, Scopus and Google Scholar databases, focusing on articles published from 2018 to April 2024. The results of the literature review indicate that local wisdom-based character education in science learning can be effectively instilled in schools by integrating the potential of local wisdom with extracurricular activities, practicums or group learning, local tourism-based learning models, game-based learning, and interactions between students using local languages.